Effect of pulmonary intervention and vitamin C supplementation on respiratory health status of people exposed to air pollution at Tirupati, Chittoor district, Andhra Pradesh - Prathiba, P. M.; Aruna, M. (International Journal Of Community Medicine And Public Health, 2024)
Background: Air pollution is a significant issue of global concern with implications for public health. The primary objective of this study was to evaluate the impact of air pollution on the respiratory health of individuals who are exposed to air pollution in Tirupati, Chittoor District, Andhra Pradesh. Methods: The present study utilised a quantitative methodology and employed a randomised control design. A total of 300 individuals using cluster sampling method were selected for this study and divided into four groups. Three of these groups received different interventions, namely pulmonary intervention, vitamin C supplementation, and a combination of pulmonary intervention and vitamin C supplementation, the fourth group served as the control group. These groups were investigated simultaneously and their outcomes were compared. Results: A notable disparity is observed in the mean scores between the pre-test and post-test measurements in the pulmonary intervention group (t=2.06, p=0.001), vitamin C supplementation group (t=3.22, p<0.001), and the combined pulmonary intervention and vitamin C supplementation group (t=3.99, p<0.000). Conversely, the control group (t=1.21, p=0.23) did not exhibit a significant difference in the pre-test and post-test mean scores. A statistically significant difference was seen in the mean post-test scores between the experimental and control groups indicated by the derived f=3.578 and a corresponding p=0.014, which met threshold for statistical significance at the p<0.05 level. Conclusions: From the study findings it is concluded that Pulmonary intervention and vitamin C supplementation has a positive impact on respiratory health status of people exposed to air pollution.